The impact of academic training programmes in improving teaching and learning: A case of academic staff at a selected university of technology - Bingwa, L.; Ngibe, M. (South African Journal of Higher Education, 2021)
Academic staff are required to change and adopt new teaching approaches to meet the requirements and expectations set by higher education institutions. This means that there is a drastic need for academics to be competent to help boost their teaching abilities, knowledge, and be encouraged to upgrade their qualifications. Without a continuous well-coordinated academic training programmes, training and skills development, academics will continuously struggle to perform their core functions which include research, teaching and learning, continuous professional development and community engagement. The intention of this study therefore, is to identify academics perceptions on academic training programmes provided by the selected university of technology and the predicaments, and the complexities involved in empowering academics to improve their teaching and learning approaches. A quantitative research approach was therefore used, with a questionnaire used as data collection instrument. Using a nonprobability purposive sampling technique, a sample size of 132 was considered. The study findings revealed that the university lacked a proper system to evaluate and measure the impact of academic training programmes offered to academic staff. The recommendations were made on different aspects in line with the findings and the study aims and objectives. But most significantly, the study recommended that a systematic review should done to monitor the impact these training programmes have towards the development and support to teaching and learning